Virtual reality-based retrospective think aloud (VR-RTA): a novel method for studying offender decision-making - Carmen-Silva Sergiou; Dominik Gerstner; Claire Nee; Henk Elffers; Jean-Louis van Gelder (Crime Science)
Abstract Objectives This article describes and tests a novel multi-method approach to examine decision-making: Virtual Reality-Based Retrospective Think-Aloud (VR-RTA). The VR-RTA method taps into the offender perspective and aims to enhance memory recall and information elicitation. Methods We applied VR-RTA among a sample of incarcerated burglars (N = 200) who scouted virtual neighborhoods to explore opportunities for burglary in immersive VR equipped with integrated eye tracking. Subsequently, they viewed a screen recording of their scouting process and simultaneously “thought aloud” about their assessment of the environment and decision-making strategies. Emerging themes were then further examined in an interview and linked to survey data. Recorded eye tracking data were used to examine burglars’ attention towards environmental features to identify deterrent and attracting cues, and were triangulated with the survey and interview data. Results Rich and detailed insights into participants’ interpretation of the environment and their decision-making strategies were obtained. VR-RTA assisted in verbalizing automated cognitive processes and increased participant engagement by building rapport. Conclusions As a multi-method approach able to capture in-the-moment considerations underlying decision-making during crime commission, VR-RTA offers potential to develop into an important tool for crime research. It is able to both overcome limitations of studies using retrospective methods, such as interviews and surveys, and contribute to the nascent field of criminological research using immersive technologies.